Distinctive physiological and molecular responses of foxtail millet and maize to nicosulfuron - Lu, Boyu; Meng, Ru; Wang, Yiru; Xiong, Wei; Ma, Yuchao; Gao, Peng; Ren, Jianhong; Zhang, Liguang; Zhao, Zhihai; Fan, Guangyu; Wen, Yinyuan; Yuan, Xiangyang (Frontiers in Plant Science, 2024)
Nicosulfuron is the leading acetolactate synthase inhibitor herbicide product, and widely used to control gramineous weeds. Here, we investigated the metabolic process of nicosulfuron into foxtail millet and maize, in order to clarify the mechanism of the difference in sensitivity of foxtail millet and maize to nicosulfuron from the perspective of physiological metabolism and provide a theoretical basis for the breeding of nicosulfuron-resistant foxtail millet varieties. We treated foxtail millet (Zhangzagu 10, Jingu 21) and maize (Nongda 108, Ditian 8) with various doses of nicosulfuron in both pot and field experiments. The malonaldehyde (MDA) content, target enzymes, detoxification enzymes, and antioxidant enzymes, as well as related gene expression levels in the leaf tissues of foxtail millet and maize were measured, and the yield was determined after maturity. The results showed that the recommended dose of nicosulfuron caused Zhangzagu 10 and Jingu 21 to fail to harvest; the yield of the sensitive maize variety (Ditian 8) decreased by 37.09%, whereas that of the resistant maize variety (Nongda 108) did not decrease. Nicosulfuron stress increased the CYP450 enzyme activity, MDA content, and antioxidant enzyme activity of foxtail millet and maize, reduced the acetolactate synthase (ALS) activity and ALS gene expression of foxtail millet and Ditian 8, and reduced the glutathione Stransferase (GST) activity and GST gene expression of foxtail millet. In conclusion, target enzymes, detoxification enzymes, and antioxidant enzymes were involved in the detoxification metabolism of nicosulfuron in plants. ALS and GST are the main factors responsible for the metabolic differences among foxtail millet, sensitive maize varieties, and resistant maize varieties.